Professor Leon Kozłowski as a man, scientist, politician and his influence into Wrocław archaeology - Burdukiewicz, Aleksandra; Burdukiewicz, Jan Michał (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The most outstanding archaeologist and professor at John Casimir University in Lviv as well as and a acknowledged politician (among others the Prime Minister (1934-1935) of the Second Republic of Poland) was Professor Leon Kozłowski (1892-1944), a student of E. Majewski from Warsaw, R.R. Schmidt from the University of Tübingen and W. Demetrykiewicz from the Jagiellonian University in Krakow. As a professor of John Casimir University he cooperated with V. Gordon Childe from the UK and H. Breuil from France, the most outstanding archaeologists in Europe at that time. His publications stand out with a clear and well-argued reasoning, great dash and thorough knowledge of the materials and concepts of the time. He was also an excellent teacher of many Polish and Ukrainian archaeologists. After 1939, he was imprisoned and tortured in the Soviet Union and Germany, where he died in unknown circumstances in 1944.
Keywords: archaeology; Lviv; Wrocław; archaeological culture; methodology